A transcomplex vision of curriculum in the context of general secondary education in Venezuela - Resplandor Barreto, Gilberto Enrique (2024)
This research aims to conduct an analysis of transversality as a curriculum theory based on the relationship between education and transversality in the curriculum, as well as some considerations on transdisciplinarity in secondary education. The process began with a review of texts related to the topic to be developed, searching for relationships between these aspects and their implications in the Venezuelan educational reality. Transversal axes have an impact on pedagogical practice by vitalizing the educational process, facilitating the integration of contents from an inter and transdisciplinary perspective. Due to the effects of globalization, the learning subject has access to a vast amount of information, which can lead to the trivialization of the learning that must be acquired in education. It is necessary to adopt educational models that are more in line with the current reality and the motivations of young people and adolescents, aiming for a more relevant, quality education.